Depression and anxiety in patients with Inflammatory Bowel Disease: A systematic review - Neuendorf, Rachel; Harding, Aubrey; Stello, Noelle; Hanes, Douglas; Wahbeh, Helané (Journal of psychosomatic research, 2016)
An increasing number of studies have been conducted to look at anxiety and depression in IBD; however, there is no clear consensus on the prevalence of anxiety and depression in this population. The objective of this systematic review was to compile the existing data on the prevalence of all mood and anxiety disorders in Inflammatory Bowel Disease patients. A series of comprehensive literature searches of Medline, Cochrane Library, PsycINFO, CINAHL, Embase, AMED, and ProQuest Dissertations were performed through March 2014. Inclusion criteria included peer-reviewed, published scientific articles that reported a measurement of mood or anxiety among IBD patients. Only studies with adults (≥18years old) and with more than 10 patients were included. Methodological quality was assessed for all included studies. 171 articles were identified with a total of 158,371 participants. Pooled prevalence estimate for anxiety disorders was 20.5% [4.9%, 36.5%] and 35.1% [30.5, 39.7%] for symptoms of anxiety. IBD patients in active disease had higher prevalence of anxiety of 75.6% [65.5%, 85.7%] compared to disease remission. Pooled prevalence of depression disorders was 15.2% [9.9%, 20.5%] and was 21.6% [18.7%, 24.3%] for symptoms of depression. The prevalence of depressive symptoms was higher in Crohn's disease (25.3% [20.7%, 30.0%]) compared to UC, and higher with active disease (40.7% [31.1%, 50.3%]) compared to IBD patients in remission. Results from this systematic review indicate that patients with IBD have about a 20% prevalence rate of anxiety and a 15% prevalence rate of depression. •We performed the largest comprehensive systematic review on the prevalence of anxiety and depression in IBD to date.•The prevalence of anxiety disorders in IBD is 21%; the prevalence of anxiety symptoms 35%.•The prevalence of depressive disorder in OBD is 15%; the prevalence of depressive symptoms is 22%.•IBD patients in active disease states have more depression and anxiety.